IMPLEMENTING LOAD BALANCING BY MODIFIED WEIGHTED ROUND ROBIN-RETRIEVE PACKET ALGORITHM ON THE SOFTWARE-DEFINED NETWORKING - ZAINAL ABIDIN; Tutuk Indriyani; Danang Haryo Sulaksono (INTEGER: Journal of Information Technology, 2018)
Clientâ€™s request for traffic problems is so huge that causes the single server difficult in handling the traffic load. Therefore, the system of load balancing is required as it is a technique to equally distribute the traffic load on the two or more connection lines so that the traffic can run optimally. Thus, the load balancing is crucial to implement by using Modified Weighted Round Robin-Retrieve Packet on the Software-Defined Networking. Based on the parameter of average response-time in time limits 0.1, 0.2, and 0.3 seconds, the scores were 0.016-0.04, 0.02-0.04, and 0.014-0.032 seconds consecutively. Based on the parameter of data transaction per second in time limits 0.1; 0.2, and 0.3 seconds, the scores respectively were 49.614-111.306, 41.678-107.032, and 37.806-102.84 data transaction/second.Â